Exfoliation and dispersion of layered materials through liquid phase processing - Lotya, Mustafa (Trinity College (Dublin, Ireland). School of Physics, 2012)
Graphene is a nanomaterial that has been the focus of intense research efforts in recent times. Production methods that yield high quality graphene without the need for detrimental chemical processing are needed in order to exploit this novel material in real-world applications. Our group makes use of ultrasound-assisted exfoliation in a liquid-phase production process that can meet this challenge. In this work, the energetics governing the dispersion of graphene in a wide range of solvents has been studied. 40 solvents were tested to show that good graphene solvents are characterised by surface tensions close to 40 mJ/m2 and Hildebrand parameter close to 23 MPa1/2. Hansen solubility parameters for graphene itself have been derived as (δD) = 18.0 MPa1/2, (δp) = 9.3 MPa1/2 and (δH) = 7.6MPa1/2. The resultant calculation of the Flory-Huggins parameter has shown that the energetic cost of exfoliation is a key parameter in governing the dispersibility of pristine graphene in solvents. Graphene dispersions in aqueous media have also been prepared with the aid of surfactant stabilisers. The dispersions were composed of largely few-layer graphene with significant quantities of mono and bilayer material observed. The dispersions were analysed using colloidal theory and the graphene flakes shown to be stabilised against re-aggregation by an electrostatic potential barrier. The graphene flakes were shown to be of extremely high quality by chemical analyses, demonstrating that oxidative treatments or other functionalisation routines are not required to produce graphene in water-based systems.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin